Dukungan Kesehatan Jiwa dan Psikososial sebagai Bentuk Intervensi Perawat Jiwa pada Penyintas Bencana Gempa Bumi - Niman, Susanti; Rita Rahayu; Adek Setiyani; Aan Somana; Siagian, Ira Octavia; Sri Nyumirah; Diah Sukaesti; Yuanita Panma; Habsyah Saparidah Agustina; Keliat, Budi Anna; Wita Oktaviana; Muchamad Ali Sodikin (Universitas Muhammadiyah Surakarta, 2023)
Mental Health and Psychosocial Support is a mental health effort for disaster survivors. Psychiatric nurses have competence in conducting it in every disaster situation. A refuge is a place for community service activities for mental nurses. Earthquake survivors who live in evacuation shelters are among the vulnerable groups experiencing mental health problems. There is a risk of mental health problems and survivors' psychosocial well-being requiring intervention from nurses. Mental health and psychosocial support by nurses can detect and prevent mental health problems and increase survivors' mental health resilience. Community service activities for natural disasters in Cianjur aim to detect early mental health problems and improve knowledge and skills in managing stress. Activities carried out in the form of group and individual mental nursing interventions. The method used is detecting mental health problems using the Self Report Questionnaire-20 (SRQ-20), providing health education through lectures, discussions and training skills regarding stress management. Activities were carried out in 4 batches and - each batch for two days. The number of survivors aged 18 and over who were intervened was 418 people from 4 villages in Cianjur Regency. The results of the SRQ-20 measurement show that 70.1% of survivors experience mental and emotional disorders. Evaluation of activities orally survivors could answer questions and demonstrate the stress management method given. Mental health and psychosocial support (DKJPS) is a standard mental nursing intervention in disaster mental nursing care. DKJPS can be applied to the practice of disaster mental nursing collaboratively by involving various scientific disciplines of nursing in the disaster area.